Optimal volume design of planetary gear train using particle swarm optimization - Daoudi, Kaoutar; Boudi, El Mostapha (2018 4th International Conference on Optimization and Applications (ICOA), 2018)
Planetary gear train are widely used for power transmission in industrial mechanic. The problem of minimum volume of simple and multi-stage planetary gear systems has been a subject of considerable interest. This paper presents a comparison between two advanced optimization algorithms known as Genetic algorithm (GA) and particle swarm optimization (PSO) to find the optimal combination of design parameters for minimum volume of planetary gear train. This study, describe the algorithm and the mathematical model the PSO technique. However, for the GA we are based on the previously published results.